P196 Percutaneous Ultrasound-Guided Biopsy of Intrathoracic Parietal Masses – a Safe Alternative to CT-Guided Biopsy?. (19th November 2012) - Simpson, TRG; Constantinescu, G; Mellor, P; Lohani, S; Khan, B; Mushtaq, M; Abdelhadi, I; Bhattacharjee, B; Serafimov, V
Abstract : Background: The current gold standard method for sampling intrathoracic lesions is via a CT-guided approach. However, most parietal-attached intrathoracic lesions can be visualised with ultrasound and sampled. Aims: A prospective audit of consecutive patients with CT-identified intrathoracic parietal-attached lesions, sampled percutaneously by an ultrasound-guided approach, was carried out to assess efficacy and safety. The lung MDT was instrumental in selecting patients. Materials and Methods: Seventeen consecutive patients were audited over a span of 8 months. This cohort included 12 males and 5 females with an age range from 42 to 84 years (median 63 years). The biopsies were performed by 4 skilled investigators assisted by a specialist nurse, using an 18 gauge single-trochar puncture under standard aseptic conditions. A Toshiba Applio ultrasound unit, with Doppler-flow map capabilities was used to avoid vessel puncture. Patients recovered in the radiology department observation ward. Results: Interpretable specimens were obtained in 16 patients. A single patient needed a repeat, successful, US-guided procedure. The median duration for the procedure was 26 minutes, with a median observation time before discharge of a further 40 minutes. Two patients developed small pneumothoraces and one patient suffered minor haemoptysis, none of which required admission. Conclusion: Where applicable, this technique is safe, fast, avoids radiation and may result in fewer complications compared to the CT-guided approach. Fewer personnel are required and CT scanner time is freed for other uses. Moreover, in the hands of an ultrasound-skilled respiratory physician, this method correctly applied would provide an earlier route to diagnosis for the Lung MDT.